Influence of neutron irradiation on the characteristics of Cu-13%wt.Al-4%wt.Ni shape memory alloy - Zengin, R; Ceylan, M (Elsevier, 2004)
Unirradiated and neutron irradiated Cu-13%wt.Al-4%wt.Ni shape memory alloy, SMA, were investigated by differential scanning calorimetry, DSC, and electrical resistivity changes, ERC, measurements, X-ray diffraction, XRD and optical microscopy methods. The forward and reverse temperatures of martensite double left right arrow austenite phase transformation decreased and transformation enthalpies increased after the neutron irradiation of samples. Some changes in the lattice parameters and surface morphologies of sample were also seen after neutron irradiation. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: neutron irradiation; shape memory alloy; transformation temperatures; lattice parameters